Pengaruh Citra Merek, Harga, dan Kualitas Produk terhadap Loyalitas Pelanggan Produk Body Lotion Nivea: Studi pada Pengikut Akun Shopee Nivea Official Store - Ratna Kusumawati Putri; Ety Dwi Susanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the influence of brand image, price and product quality on customer loyalty to Nivea body lotion products (study of followers of the Shopee Nivea Official Store account). The method used in this research is a quantitative type method. The population in this study were followers of the Shopee Nivea Official Store account. The sample used was 100 taken using purposive sampling technique. Based on the results of the data processing, in the F test it can be stated that the calculated F is 22,476 > F table 2.699 with a significance level of 0.000 < 0.05. So the results of the F test show that the variables Brand Image, Price and Product Quality simultaneously influence Customer Loyalty. In the t test, the sig value for the brand image variable (X1) is 0.000 < 0.05. The calculated t value is 7.781 > t table 1.984. So H0 is rejected and H1 is accepted, meaning that the Brand Image variable partially influences Customer Loyalty. The sig value of the Price variable (X2) is 0.004 < 0.05. The calculated t value is -2.964 < t table 1.984. So H0 is rejected and H2 is accepted, meaning that the Price variable has a partial negative effect on Customer Loyalty. The significance value for the Product Quality variable (X3) is 0.000 < 0.05. The calculated t value is -4.086 < t table 1.984. So H0 is rejected and H3 is accepted, meaning that the Product Quality variable has a partial negative effect on Customer Loyalty.